The financing of medicines in Brazilian municipalities: whose responsibility is it? - Wendell Rodrigues Oliveira da Silva; Rodrigo Fonseca Lima; Ivanessa Thaiane do Nascimento Cavalcanti; Rafael Santos Santana; Silvana Nair Leite (Universidade de São Paulo, 2024)
ABSTRACT OBJECTIVE To analyze the investments made in medicines by the federated entities and the asymmetries in these investments from 2016 to 2020, which may have an impact on the supply of and access to these medicines in the SUS. METHODS This is an exploratory, retrospective study to identify who are the main entities responsible for investment in Primary Care medicines in municipalities, the evolution, counterparts, and regional differences of this investment between 2016 and 2020. RESULTS The amounts spent on medicines by Brazilian municipalities were higher than the contribution to the CBAF from the MS or the MS + State in all the years analyzed. The average percentages of federal funds transferred and municipal spending varied according to the region of Brazil. The average per capita amount invested in medicines by municipalities increased between 2016 and 2020 (deflation applied), with a greater impact for municipalities with lower MHDI. The Farmácia Popular program mainly reaches municipalities with the largest populations and the highest MHDI and is therefore not enough to address the inequalities in access pointed out. CONCLUSIONS There has been a widening of inequalities in the capacity of municipalities to ensure access to medicines, especially among the most vulnerable municipalities, accumulating even more risks of illnesses and deaths from primary care-sensitive diseases.